Precise Measurement of Polarization Variation Using Weak Measurement With Double Pointers - Lan Luo; Yu He; Junfan Zhu; Liang Fang; Bo Liu; Zhiyou Zhang (IEEE Photonics Journal)
In this paper, a weak measurement scheme with double pointers (mean value shift and intensity shift of the post-selected light) is presented to simultaneously measure the tiny polarization change (phase and amplitude) of light in a single experimental apparatus. Furthermore, rather than using charge-coupled-device (CCD) to measure the pointer shift, we use the two-channel photoreceiver combined with lock-in amplifier (LIA) to measure the intensities of a split-Gaussian mode in this work. In this way, we introduce two intensity contrast ratios (ICRs) as special pointers to characterize the mean value and intensity shifts. As a result, the measurement precision of the polarization rotation is on the order of magnitude of $\,10^{-7}rad$ in the experiment. These findings provide a distinctive insight into the weak measurement and have important implications for the accurate measurement of complex optical parameters.